Economic growth in Belarus: what lies beneath the stylized facts - Kruk, Dzmitry E. (Journal of the Belarusian State University. Economics, 2018)
This article deals with the assessment of long-run growth environment in Belarus. The paper provides evidence and stylized facts about Belarusian growth. It shows that Belarusian long-run growth rate in 1997–2016 was rather high, but experienced unsustainability. Estimates and indicators presented in the study witness that the unsustainability stems from the lack of productivity fundamentals. A number of recommendations on growth enhancing policy has been formulated in the study, which would allow strengthening growth potential in Belarus.
Keywords: economic growth; Belarus; total factor productivity; (dis)embodied technological progress